Lake Afrera, a structural depression in the Northern Afar Rift (Red Sea) - Enrico Bonatti; Elia Gasperini; Luigi Vigliotti; Luca Lupi; Orlando Vaselli; Alina Polonia; Luca Gasperini (Heliyon, 2017)
The boundary between the African and Arabian plates in the Southern Red Sea region is displaced inland in the northern Afar rift, where it is marked by the Red Sea-parallel Erta Ale, Alaita, and Tat Ali volcanic ridges. The Erta Ale is offset by about 20 and 40 km from the two en echelon ridges to the south. The offset area is highly seismic and marked by a depression filled by lake Afrera, a saline body of water fed by hydrothermal springs. Acoustic bathymetric profiles show ≈80 m deep canyons parallel to the NNW shore of the lake, part of a system of extensional normal faults striking parallel to the Red Sea. This system is intersected by oblique structures, some with strike-slip earthquakes, in what might evolve into a transform boundary. Given that the lake’s surface lies today about 112 m below sea level, the depressed (minus ≈190 m below sea level) lake’s bottom area may be considered the equivalent of the “nodal deep” in slow-slip oceanic transforms. The chemistry of the lake is compatible with the water having originated from hydrothermal liquids that had reacted with evaporites and basalts, rather than residual from evaporation of sea water. Bottom sediments include calcitic grains, halite and gypsum, as well as ostracod and diatom tests. The lake’s level appears to have dropped by over 10 m during the last ≈50 years, continuing a drying up trend of the last few thousand years, after a “wet” stage 9,800 and 7,800 years before present when according to Gasse (1973) Lake Afrera covered an area several times larger than at present. This “wet” stage corresponds to an early Holocene warm-humid climate that prevailed in Saharan and Sub Saharan Africa. Lake Abhé, located roughly 250 km south of Afrera, shows similar climate-driven oscillations of its level.